The Kallikrates vs the Kapodistrias Reforms in Greece: A Story of Moderate Success - Kalimeri Vasiliki (Sciendo, 2018)
This article aims to analyse and evaluate the implementation of Greek local government reforms based on the surrounding economic and political situation. The main two reforms in question, the Kapodistrias and the Kallikrates programmes, both tried to modernise the state under the influence of Greece’s European Union membership. Though revolutionary for its era, the Kapodistrias programme soon reached its limits. The newer Kallikrates reform, adopted under pressure from the European Union and the International Monetary Fund due to the economic crisis, has sought to reduce public spending and create a leaner state. Nevertheless, largely because of its external origins, even this more recent reform has failed to improve the deteriorating Greek local government sector.